Managers and Moral Dissonance: Self Justification as a Big Threat to Ethical Management? - Lowell, Jonathan (2012)
This article discusses the implications of moral dissonance for managers, and how dissonance induced self justification can create an amplifying feedback loop and downward spiral of immoral behaviour. After addressing the nature of moral dissonance, including the difference between moral and hedonistic dissonance, the writer then focuses on dissonance reduction strategies available to managers such as rationalization, self affirmation, self justification, etc. It is noted that there is a considerable literature which views the organization as a potentially corrupting institution and a source of acute levels of moral dissonance. A simplified process model linking immoral behaviour, dissonance and rationalization is mooted, and some recent theories which question traditional dissonance models, including the free choice paradigm (FCP), are considered. The writer concludes that in the light of the above mentioned critical theories, it may be assumed that the levels of moral dissonance, and the extent of rationalization/self justification amongst managers, are more a function of personality and situational factors than previously assumed.
Keywords: Free choice paradigm; Self justification; Moral dissonance; Cognitive Dissonance; Morality; Management